MTA2 promotes the metastasis of esophageal squamous cell carcinoma via EIF4E‐Twist feedback loop. Issue 3 (19th January 2021) - Dai, Su‐Li; Wei, Si‐Si; Zhang, Cong; Li, Xiao‐Ya; Liu, Yue‐Ping; Ma, Ming; Lv, Hui‐Lai; Zhang, Zhenzhen; Zhao, Lian‐Mei; Shan, Bao‐En
Abstract: Metastasis‐associated protein 2 (MTA2) is frequently amplified in many types of cancers; however, the role and underlying molecular mechanism of MTA2 in esophageal squamous cell carcinoma (ESCC) remain unknown. Here, we reported that MTA2 is highly expressed in ESCC tissue and cells, and is closely related to the malignant characteristics and poor prognosis of patients with ESCC. Through in vitro and in vivo experiments, we demonstrated that MTA2 significantly promoted ESCC growth, metastasis, and epithelial‐mesenchymal transition (EMT) progression. This integrative analysis combined with expression microarray showed that MTA2 could interact with eukaryotic initiation factor 4E (EIF4E), which positively regulates the expression of Twist, known as a master regulator of EMT. Moreover, the results of chromatin immunoprecipitation revealed that MTA2 was recruited to the E‐cadherin promoter by Twist, which reduced the acetylation level of the promoter region and thus inhibited expression of E‐cadherin, and subsequently promoted the aggressive progression of ESCC. Collectively, our study provided novel evidence that MTA2 plays an aggressive role in ESCC metastasis by a novel EIF4E‐Twist positive feedback loop, which may provide a potential therapeutic target for the management of ESCC. Abstract : We demonstrated that the upregulation of MTA2 in ESCC was significantly correlated with malignant characteristics and poor survival probability of patients. The abnormal expression of MTA2 in ESCC contributed to the proliferation, metastasis, and EMT phenotype of ESCC cells through a novel EIF4E‐Twist positive feedback loop.